The good In fashion : redefining fashion goals - Soh, Belle Si Yu (Nanyang Technological University, 2020)
The Good In Fashion (TGIF) is a communications campaign that aimed to encourage Singaporeans aged 21 to 29 to prolong the lifespan of their clothing. In 2018, Singapore produced over 219,800 tonnes of textile and leather waste, of which only 6% is recycled — the second-lowest recycling rate after plastic. This was due to factors such as the overconsumption of fast fashion and high throwaway culture in Singapore. Given the scarce land resources Singapore has, this has become a pertinent issue to address as the Semakau landfill is predicted to last only till the year 2035. This presents the need to promote an alternative and more sustainable mode of fashion consumption in order to alleviate the problem of textile waste in Singapore. Hence, as guided by the Social Cognitive Theory, the campaign sought to promote four sustainable fashion behaviours: buying second-hand, swapping, donating and reselling. This was achieved through both online and on-ground tactics that were formulated based on the strategic pillars of ‘Educate’, ‘Empower’ and ‘Engage’. During the course of four months, TGIF was successful in raising awareness about the negative impacts of fast fashion consumption as well as boosting our target audience’s intention to adopt sustainable fashion. The campaign also achieved significant digital traction, attaining a total of 365,314 impressions across all social platforms, and a 6.74% and 4.48% engagement rate on Instagram and Facebook respectively. This paper will present a comprehensive analysis of the local textile waste issue using a combination of both secondary and formative research findings, followed by the details of our campaign strategy from the development to evaluation stages. The report will then conclude with a summative discussion of our limitations, recommendations, and plans for future campaign sustainability.